Rapid, Large, and Synchronous Sweat and Cardiovascular Responses Upon Minor Stimuli in Healthy Subjects. Dynamics and Reproducibility - Ho, Ai Van Thuy; Toska, Karin; Wesche, Jarlis (Frontiers in Neurology, 2020)
Purpose: The aim of the study was to investigate steady state levels, dynamics and reproducibility of cardiovascular variables and electrodermal activity in different skin areas in response to minor physiological and mental stimuli in healthy subjects in the thermoneutral zone, carried out in high time resolution. Methods: Thirteen healthy subjects underwent experiments on two separate days. Noninvasive electrodermal activity in five different skin areas was measured continuously using a skin conductance method, including resting supine and sitting positions, performing deep inspirations, a mental challenge and being exposed to a sudden loud sound. Blood pressure, heart rate, radial artery blood flow and skin perfusion were measured simultaneously. Results: Electrodermal activity in the right and left palms was almost identical, with rapid and large increases within a few seconds in response to stimuli, whereas no such significant changes were seen in the face, back and abdomen. Radial artery blood flow and palmar skin perfusion changed synchronously with electrodermal activity for each stimulus, and were correlated to changes in blood pressure and heart rate. The response patterns in each subject were very similar on the two experimental days. There was very low spontaneous electrodermal activity in the supine position, contrary to the resting sitting position. Conclusion: The electrodermal activity increased rapidly and synchronously in both palms within a few seconds as a response to minor physiological and mental stimuli, synchronous with fluctuations in radial artery blood flow, palmar skin perfusion and cardiovascular variables. The responses are reproducible from day to day, making them a stable and constant stimuli to be used for studies in patients with hyperhidrosis.